European Influences: Edwin Muir, Kafka, and the Spirit of Italy - McCulloch, Margery Palmer (Complutense Journal of English Studies, 2014)
Starting from Orkney-born Edwin Muir’s article “North and South,” published in the American Freeman magazine in 1922, this essay will explore Muir’s involvement with the life and thought of Europe throughout his life and his work as poet, novelist, translator, and critic; and his particular fascination with what he saw as the philosophical difference between the European peoples of the north and the south in relation to their contrasting perceptions of Time and the idea of Fate in human lives. The essay will discuss Muir’s relationship with the work of Franz Kafka, whose novels Muir and his wife Willa were the first to translate into English, and the effect of this relationship with Kafka and the city of Prague on his own poetry. It will also explore the contrasting southern influence of Italy, and the city of Rome where Muir went as Director of the British Council Institute in 1949. The paper will conclude with a consideration of what it is in Muir’s poetry and thought which marks him out as the European modernist poet the later Seamus Heaney considered him to be, and which also makes him a poet of continuing relevance to our own times.